35. NUTRITIONAL KNOWLEDGE, PRACTICES, AND RELATED FACTORS AMONG TYPE 2 DIABETES OUTPATIENTS AT 19-8 HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Background: Nutritional knowledge and dietary practice adherence play a crucial role in glycemic control among patients with type 2 diabetes mellitus. Numerous studies conducted both domestically and internationally have indicated that nutritional knowledge and dietary practice adherence among patients with type 2 diabetes mellitus remain limited. However, to date, no comprehensive study has been conducted to assess this issue at 19-8 Hospital.Objectives: This study aimed to assess nutritional knowledge, dietary practice adherence, and associated factors among outpatients with type 2 diabetes mellitus at 19-8 Hospital.Methods: A descriptive cross-sectional study was conducted on 400 outpatients with type 2 diabetes mellitus at 19-8 Hospital. Data were collected through face-to-face interviews using a standardized and validated questionnaire.Results: A total of 54.75% of patients demonstrated adequate nutritional knowledge, and 55.5% adhered appropriately to dietary recommendations. Nutritional knowledge and dietary practice adherence were significantly associated with age (OR = 3; p < 0.05), access to health information (OR = 2.3; p = 0.0001), education level, and marital status (for dietary practice adherence) (p < 0.05).Conclusion: Nutritional knowledge and dietary practice adherence among patients with type 2 diabetes mellitus at 19-8 Hospital remain limited. Enhancing personalized nutrition counseling and strengthening health education and communication are essential strategies to improve dietary adherence among these patients.
Keywords: Type 2 Diabetes Mellitus; Dietary Adherence; nutritional knowledge; dietary practices.